TorsinA protein and neuropathology in early onset generalized dystonia with GAG deletion - Rostasy, Kevin; Augood, Sarah J; Hewett, Jeffrey W; Leung, Joanne Chung-on; Sasaki, Hikaru; Ozelius, Laurie J; Ramesh, Vijaya; Standaert, David G; Breakefield, Xandra O; Hedreen, John C (Neurobiology of disease, 2003)
Familial, early onset, generalized torsion dystonia is the most common and severe primary dystonia. Most cases are caused by a 3-bp deletion (GAG) in the coding region of the TOR1A ( DYT1) gene, which is widely expressed in human brain and encodes the protein torsinA. This study compares neuropathology and torsinA expression in the normal human brain with that in dystonia cases with and without the GAG deletion. TorsinA-like protein was expressed in neuronal cytoplasm throughout the human brain, including cerebellum, substantia nigra, hippocampus, and neostriatum, with higher levels in specific neurons. This immunostaining pattern was not discernibly different in dystonia and normal brains in midbrain and neostriatal regions. However, nigral dopaminergic neurons appeared to be larger in both GAG-deletion and non-GAG-deletion dystonia brains compared to normal, and may be more closely spaced in GAG-deletion brains. Beyond these apparent changes in neuronal size and spacing in dystonia brains, there was no indication of neuron loss, inflammation, DNA strand breaks, or altered distribution of torsin-like immunoreactivity, supporting a functional rather than degenerative etiology of early onset torsion dystonia.